Measurement of J/ψ polarization in pp collisions at √s = 7 TeV - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; Grünberg, Oliver; et al. (The European physical journal. C, Particles and fields, 2013)
An angular analysis of the decay J/ψ→μ+μ− is performed to measure the polarization of prompt J/ψ mesons produced in pp collisions at √s = 7 TeV. The dataset corresponds to an integrated luminosity of 0.37 fb−1 collected with the LHCb detector. The measurement is presented as a function of transverse momentum, pT, and rapidity, y, of the J/ψ meson, in the kinematic region 2<pT<15 GeV/c and 2.0<y<4.5.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, O. Grünberg, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, B. Leverington, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 591
Gesehen am 21.04.2021